GERMAN FILM “FACK JU, GÖHTE”: THE IDEA OF FREEDOM EDUCATION IN GERMANY - Regina Angelica Kezia; Mugijatna Mugijatna; Wakit Abdullah Rais (Proceeding of International Conference on Art, Language, and Culture, 2017)
The film “Fack Ju, Göhte” is a comedy film produced in 2013, which could attract three million people in its first 17 day of screening, and regarded as the most successful film in Germany then. This film tells the story about an ex-convict, Zeki Müller, who disguises himself as areplacement teacher to obtain a hidden money stash in the building of Göthe Gesamtschule. However the ambience of the class and the students who Zeki teaches, garner sympathy for him from his students with teaching style people calls as “unique” at least and “maverick” at best. Zeki becomes the favourite teacher at his school and he manages to increase the school’s ranking in the town. This writting has a purpose to describe the idea of freedom in education field is potrayed in the film“Fack Ju, Göhte”. The method used is qualitative method with contain analysis, and data gathering technique used is literary study. The theory used are semiotics theory from C.S Peirce. The result of this research shows that the film “Fack Ju, Göhte” use this film as one of their education media, a new standpoint in portraying the education field which is the idea of freedom and self expression for the learners.